Associations of TGFBR1 and TGFBR2 gene polymorphisms with the risk of hypospadias: a case–control study in a Chinese population. Issue 5 (6th October 2017) - Han, Xin-Rui; Wen, Xin; Wang, Shan; Hong, Xiao-Wu; Fan, Shao-Hua; Zhuang, Juan; Wang, Yong-Jian; Zhang, Zi-Feng; Li, Meng-Qiu; Hu, Bin; Shan, Qun; Sun, Chun-Hui; et al.
Abstract : This case–control study investigated the association of transforming growth factor-β (TGF-β) receptor type I and II ( TGFBR1 and TGFBR2 ) gene polymorphisms with the risk of hypospadias in a Chinese population. One hundred and sixty two patients suffering from hypospadias were enrolled as case group and 165 children who underwent circumcision were recruited as control group. Single nucleotide polymorphisms (SNPs) in TGFBR1 and TGFBR2 genes were selected on the basis of genetic data obtained from HapMap. PCR-restriction fragment length polymorphism (PCR-RFLP) was performed to identify TGFBR1 and TGFBR2 gene polymorphisms and analyze genotype distribution and allele frequency. Logistic regression analysis was conducted to estimate the risk factors for hypospadias. No significant difference was found concerning the genotype and allele frequencies of TGFBR1 rs4743325 polymorphism between the case and control groups. However, genotype and allele frequencies of TGFBR2 rs6785358 in the case group were significantly different in contrast with those in the control group. Patients carrying the G allele of TGFBR2 rs6785358 polymorphism exhibited a higher risk of hypospadias compared with the patients carrying the A allele ( P <0.05). The TGFBR2 rs6785358 genotype was found to be significantly related to abnormal pregnancy and preterm birth (both P <0.05). The frequency of TGFBR2 rs6785358 GG genotype exhibited significant differences amongst patients suffering from four different pathological types of hypospadias. Logistic regression analysis revealed that preterm birth, abnormal pregnancy, and TGFBR2 rs6785358 were the independent risk factors for hypospadias. Our study provides evidence that TGFBR2 rs6785358 polymorphism might be associated with the risk of hypospadias.